2021
DOI: 10.1002/tox.23398
|View full text |Cite
|
Sign up to set email alerts
|

Subacute exposure to aluminum chloride causes prolonged morphological insults in the ventral male prostate and in the female prostate of adult gerbils

Abstract: Aluminum (Al) is a widespread metal in the environment, and is found in fresh or processed foods, household utensils, packaging, and medicines. In addition to its high toxicity, Al can also have estrogenic agonistic effects on target organs. Considering that the Al effects on the prostate are little known, the aim of this study was to evaluate the impact of aluminum chloride (AlCl 3 ) subacute exposure on the morphophysiology of the male ventral prostate and the female prostate of adult gerbils. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The present study's histological assessments consistently revealed adverse impacts on the reproductive system in the testis, epididymis, and prostate. For instance, da Silva Lima et al [12] documented disruptions in part of the seminiferous tubules within the testes, epithelial hyperplasia, and the accumulation of lipofuscin granules in secretory luminal cells within the prostate of gerbils treated with 10 mg/kg.BW AlCl3 for 30 days. Interestingly, these specific effects were not observed in our study with rats exposed to 1 mg/L Al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study's histological assessments consistently revealed adverse impacts on the reproductive system in the testis, epididymis, and prostate. For instance, da Silva Lima et al [12] documented disruptions in part of the seminiferous tubules within the testes, epithelial hyperplasia, and the accumulation of lipofuscin granules in secretory luminal cells within the prostate of gerbils treated with 10 mg/kg.BW AlCl3 for 30 days. Interestingly, these specific effects were not observed in our study with rats exposed to 1 mg/L Al.…”
Section: Discussionmentioning
confidence: 99%
“…While initial studies on aluminum suggested potential biological significance, over the last two decades, numerous studies have contradicted this notion. Recent research has consistently demonstrated the lack of bio-utility of this metal, emphasizing its association with adverse effects on various target organs, including the kidneys [4], brain [5,6], and the male and female reproductive systems [3,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Present study's histological assessments consistently revealed adverse impacts on the reproductive system in the testis, epididymis, and prostate. For instance, da Silva Lima et al [12] documented disruptions in part of the seminiferous tubules within the testes, epithelial hyperplasia, and the accumulation of lipofuscin granules in secretory luminal cells within the prostate of gerbils treated with 10 mg/kg.BW AlCl3 for 30 days. Interestingly, these specific effects were not observed in our study with rats exposed to 1 mg/L Al.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a recent study by our research group showed that Al neonatal exposure impaired the prostate development pattern in 15‐day‐old gerbils (Gomes et al, 2020). Furthermore, Al subacute exposure during adulthood also caused tissue insult and oxidative stress in the prostate of male and female gerbils (Silva Lima et al, 2020, 2022). However, it is not known whether the morphological damage caused by Al in neonates is permanent and persists during adult and senile life.…”
Section: Introductionmentioning
confidence: 99%